The microscopic identification of mammal species from hair samples - Chaka, Konute Jackson (University of the Free State, 2004)
The expansion of the game ranching industry in South Africa has benefited predators such as the leopard through expanding habitat availability and increased divesity availability of prey animals. In view of the value of game, especially rare game species, losses due to predators are often viewed by land owners in a more serious light than stock losses. This has led to increased prosecution of predators such as the leopard. In an attempt to address the conflict between predators and game- and livestock farmers, a research project on leopards was initiated in the Limpompo Province, South Africa (Smit 2002; Van Wyk 2003). As part of this larger research project, the need has arisen to be able to identify the remains of mammal prey species in the feaces of leopards. A list of fourty expected prey mammal species that potentially occur in the northern savanna areas of South Africa was compiled. They covered a broad range of families, namely bovidae, viverridae, procaviidae, mustelidae, gliridae, muridae, suidae, leporidae, orycteropodidae, sciuridae, felinae, cercopithecidae and thryonomyidae. The objectives of this study were to prepare hair samples from these selected mammal species for microscopic analyses with a view to obtain detailed illustrations of the cuticular scale patterns and cross-sections of the hair, to study and describe the taxonomic features of the hair of the various mammal species and to compile a key that can assist with the identification of these mammal species from microscopic analyses of hair samples. Hair samples were taken from the dried skins of specimens of the selected mammal species that were hosted in the Transvaal Museum in Pretoria. A study was also conducted to determine if the characteristics of hair from distinctly different body parts of mammals differ. The impala was selected for this study in view of its importance as a preferred prey species of the leopard in the northern savanna of South Africa. Hair samples for this study were obtained from a fresh impala carcass. After preparation of the hair samples, the cuticular scale patterns were photographed using a scanning electron microscope. Cross-sections of the hair were photographed with a Nikon light microscope. In this study, mainly the guard hair of the mammal species were considered for study since they showed the most distinct variation in shape and characteristics. The four features of hair morphology that were considered the most important for identification, are the cuticular scale patterns, the cross-section shape of the hair itself, the cortex and medulla. The colour of the hair and the appearance and distribution of the pigments can sometimes serve as aids to identification and in this study pigmentation was considered in the description of the cross-section of the hair. The hair of the impala taken from the different body parts varied in colour. Microscopic examination of hair structure from the different body parts revealed a number of differences namely the cross-section shapes, diameter of hair and the pigmetation of the cortex, but the scale patterns of hair from the different hair body parts were found to be very similar. The only exceptions were hair from the brisket and foreleg that differed from the hair of the rest of the body. A key using the taxonomic characteristics of the hair, was compiled to assist in the identification of the thirty-nine mammal species. Since the key does not always key out on individual species, it is recommended that the key only be used to narrow down the number of possible species. For the final identification the detailed description of the hair must be consulted

Die uitbreiding van die wildbedryf in Suid-Afrika het roofdiere soos die luiperd bevoordeel deur groter habitat beskikbaarheid en die groter getal en diversiteit prooi wat beskikbaar is. In die lig van die waarde van wild, veral skaars wildspesies, beskou grondeienaars wildver1iese deur roofdiere dikwels in 'n meer emstige lig as veever1iese. Dit het tot verskerpte jagmakery op roofdiere soos die luiperd gelei. In 'n poging om die konflik tussen roofdiere en wild- en veeboere aan te spreek, is 'n navorsingsprojek op luiperds in die Limpopo Provinsie van Suid-Afrika geloods (Smit 2002, Van Wyk 2003). As deel van hierdie groter navorsingsprojek het die behoefte onstaan om die oorblyfsels van soogdierprooi in die mis van luiperds te kan identifiseer. 'n Lys van nege-en-dertig soogdierspesies wat potensieel in die noordelike savanna dele van Suid-Afrika kan voorkom is saamgestel. Hulle sluit 'n wye verskeidenheid van families in, naamlik bovidae, viverridae, procaviidae, mustelidae, gliridae, muridae, suidae, leporidae, orycteropodidae, sciuridae, felinae, cercopithecidae en thryonomyidae. Die doelstellings van die studie was om haarmonsters van hierdie geselekteerde soogdierspesies vir mikroskopiese analise voor te berei ten einde gedetaileerde illustrasies van die kutikulere skubpatrone en die dwarsdeursnee van die hare te verkry, tweedens om die taksonomiese eienskappe van die hare van die onderskeie soogdierspesies te bestudeer en te beskryf, en laastens om 'n identifikasiesleutel saam te stel wat die identifikasie van soogdiere vanaf mikroskopiese analise van haarmonsters sal vergemaklik. Haarmonsters is geneem van droe huide van die geselekteerde soogdierspesies wat in die Transvaal Museum in Pretoria gehuisves word. A studie is ook ondemeem om te bepaal of die eienskappe van hare afkomstig van verskillende liggaamsdele van soogdiere, verskil. Die rooibok is vir hierdie studie gekies aangesien dit so 'n belangrike prooispesie van die luiperd in die noordelike savanna dele van Suid-Afrika is. Die haarmonsters vir hierdie studie is van 'n vars rooibok karkas verkry. Na voorbereiding van die haannonsters is die kutikulere skubpatrone met behulp van 'n skanderings-elektronmikroskoop gefotografeer. Die dwarsdeursnit van die hare is met behulp van 'n Nikon ligmikroskoop gefotografeer. In hierdie studie is hoofsaaklik skuthare vir die studie gebruik aangesien hulle die duidelikste verskille in vonn en eienskappe toon. Die vier eienskappe van haarmorfologie wat as die belangrikste vir identifikasie beskou is, is die kutikulere skubpatrone, die vonn van die hare op die dwarsdeursnit, die korteks en die medulla. Die kleur van die hare en die voorkoms en verspreiding van die pigmente kan soms as hulpmiddel gebruik word, en in hierdie studie is pigmentasie in ag geneem by die beskrywing van die dwarsdeursnit van die hare. Die hare afkomstig van die onderskeie liggaamsdele van die rooibok het verskil in kleur. Mikroskopiese analise van die haarstruktuur het 'n aantal verskille getoon, maar daar is gevind dat die skubpatrone min van mekaar verskil het. Die enigste uitsonderings was die hare afkomstig van die bors en voorbene wat verskil het van die van die res van die liggaam. 'n Sleutel wat berus op die taksonomiese eieskappe van die hare is saamgestel om met die identifisering van die neg~n-dertig soogdierspesies behulpsaam te wees. In die lig van die feit dat die sleutel nie in alle gevalle lei tot die seleksie van slegs een spesie nie, word daar aanbeveel dat die sleutel slegs gebruik word om die moontlike spesies te venninder tot 'n kleiner getal. Vir die finale identifikasie moet die gedetaileerde beskrywing van die hare geraadpleeg word.
Dissertation (M.Sc. Agric. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 2004
Keywords: Body parts; Cortex; Medulla; Prey; Scale patterns; Taxonomy; Predators